2000
DOI: 10.1002/jlb.67.2.259
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 activity is negatively regulated by cannabinol through inhibition of its protein components, c-fos and c-jun

Abstract: Regulation of the activator protein-1 (AP-1) complex is very intricate because it involves phosphorylation state, protein-protein, and protein-DNA interactions. In these studies, the regulation of AP-1 activity, with emphasis on c-fos and c-jun regulation, was investigated using cannabinol (CBN) in primary mouse splenocytes in vitro. Cannabinoid compounds exhibit immunosuppressive actions that are putatively mediated through Gi-protein coupled receptors that negatively regulate adenylate cyclase. However, rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…It has also been reported that cannabinol exhibited a 10-fold higher affinity for the CB2 receptor, the predominant cannabinoid receptor expressed in the immune system (Bouaboula et al, 1993;Galiegue et al, 1995;Schatz et al, 1997). Indeed, cannabinol exhibits immunomodulating effects (Condie et al, 1996;Herring et al, 1998;Faubert and Kaminski, 2000;Yea et al, 2000), but, as demonstrated here, so did cannabidiol and WIN 55212-3, both of which exhibit low binding affinity for CB1 and CB2.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…It has also been reported that cannabinol exhibited a 10-fold higher affinity for the CB2 receptor, the predominant cannabinoid receptor expressed in the immune system (Bouaboula et al, 1993;Galiegue et al, 1995;Schatz et al, 1997). Indeed, cannabinol exhibits immunomodulating effects (Condie et al, 1996;Herring et al, 1998;Faubert and Kaminski, 2000;Yea et al, 2000), but, as demonstrated here, so did cannabidiol and WIN 55212-3, both of which exhibit low binding affinity for CB1 and CB2.…”
Section: Discussionsupporting
confidence: 69%
“…1, interleukin-2 was readily induced by PMA/Io treatment and was inhibited by cannabinol (1-20 M) in a concentration-dependent manner. These studies were conducted with micromolar concentrations of cannabinoid compounds because it has been previously demonstrated that these concentrations are required in vitro due to both the lipophilicity of the cannabinoids and the serum concentration dependence for many of the cannabinoid effects (Faubert and Kaminski, 2000). Pretreatment of splenocytes with a combination of antagonists (0.5 M/0.5 M, 2.5 M/2.5 M, and 5 M/5 M SR144528/SR141716A) did not significantly attenuate the cannabinol-mediated inhibition of interleukin-2 production at any cannabinol concentration tested.…”
Section: Effect Of Cannabinoid Receptor Antagonists Onmentioning
confidence: 99%
See 3 more Smart Citations